2018
DOI: 10.18201/ijisae.2018648455
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Diagnosis by Different Machine Learning Methods Using Blood Analysis Data

Abstract: Today, one of the most common types of cancer is breast cancer. It is crucial to prevent the propagation of malign cells to reduce the rate of cancer induced mortality. Cancer detection must be done as early as possible for this purpose. Machine Learning techniques are used to diagnose or predict the success of treatment in medicine. In this study, four different machine learning algorithms were used to early detection of breast cancer. The aim of this study is to process the results of routine blood analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 22 publications
(27 reference statements)
0
21
0
1
Order By: Relevance
“…Extreme learning machine [78] 80.00% PySpark and its machine learning frameworks [79] 83.0% Classification via regression [80] 80.0% Proposed model 86.97% Table A3) was 86.97%, as applied to the BCCD data set. Furthermore, a comparison of the results of six methods (Table II) using the same data set suggested that the proposed method is clearly superior.…”
Section: Resultsmentioning
confidence: 99%
“…Extreme learning machine [78] 80.00% PySpark and its machine learning frameworks [79] 83.0% Classification via regression [80] 80.0% Proposed model 86.97% Table A3) was 86.97%, as applied to the BCCD data set. Furthermore, a comparison of the results of six methods (Table II) using the same data set suggested that the proposed method is clearly superior.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, there are many studies about artificial intelligence employed for various purposes like Alzheimer’s disease diagnosis, cancer estimation, biopsy and dermoscopy analysis etc. [31] , [32] , [33] , [34] , [35] . In recent times, the COVID-19 pandemic creates heavy work on health workers.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, many different approaches have been tried in the literature for the detection of breast cancer using the BCC dataset ( Table 1). The results of the BO-KNN model were compared with the models developed by Patrício et al [17], Li [18], Aslan et al [19], Singh [4], Akben [20], and Silva Araújo et al [21]. In all of these studies, the same number of subjects (116) were used with different input combinations and data division strategies.…”
Section: Summary Of Results and Comparison With Literaturementioning
confidence: 99%
“…Assiri and Kamel [16] examined the serum leptin, resistin and visfatin levels as risk factors for postmenopausal breast cancer. As shown in Table 1, extensive studies have been conducted on the Breast Cancer Coimbra (BCC) dataset in recent years [4,[17][18][19][20][21]. Patrício et al [17] constructed LR, random forest (RF), and support vector machine models (SVM) models using glucose, age, resistin, and BMI features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation